HIP Fracture REhabilitation Program for older adults with hip fracture (HIP-REP) based on activity of daily living: a feasibility study - Alice Røpke; Anne-Le Morville; Trine Elleby Møller; Emma Cæcilie Guttzeit Delkus; Carsten Bogh Juhl (BMC Geriatrics, 2022)
Abstract Background A Rehabilitation Program for older adults with hip fracture (HIP-REP) based on Activity of Daily Living has been developed. The objectives of this study were to assess the feasibility and safety of the HIP-REP program to inform a future randomized controlled trial (RCT). Methods A feasibility study Inspired by the Complex-intervention development (Medical Research Council framework phase II) design using quantitative and qualitative research methods were conducted. Eighteen participants (above 65 years) with hip fracture were recruited from the orthopedic wards. The setting was cross sectoral including Copenhagen University Hospital, Herlev and Gentofte and rehabilitation centers in Herlev, Gentofte and Lyngby-Taarbæk municipalities. A cross-sectoral rehabilitation intervention tailored to the needs of older adults with hip fracture highlighting systematic goal setting and strategies focused on activities of daily living was conducted. Pre-defined feasibility criteria: participants recruitment and retention, duration of measuring the outcome, adherence to intervention, and adverse events, along with self-reported outcomes and an objective measurement of performance in activity of daily living. Focus groups were analyzed using a deductive manifest content analysis approach. Descriptive statistical analysis and paired t-tests were performed for assessing change in outcome measures. Results Recruitment rate was 4.5/month. Outcome measures were performed but length and number of questionnaires were a burden. Thirteen out of eighteen participants completed the study three dropped out and two died. Adherence among the 13 was 100%. Focus group revealed issues regarding coordinating the intervention, ensuring procedural processes across sectors regarding recruitment of participants, and documentation in the database. Participants expressed satisfaction with the intervention and felt safe during intervention. Assessment of Motor and Process Skills showed better increase between (range 0.4 to 1.6) in ADL motor ability measures and better increase between (range 0.4 to 0.7) for process ability. No clear association between outcome improvements and intervention adherence. Conclusions The cross-sectoral intervention based on daily activities was feasible and safe for older adults with hip fracture. A future RCT, with an improved recruitment strategy and reduced number of outcome measures will evaluate the effectiveness in improving independence and safety performance of activity of daily living. Trial registration ClinicalTrials.gov ID: NCT03828240 . Registered on January 29, 2019.